Land cover and fire accounts to support Indigenous land management: A pilot study of Yawuru Country. (1st July 2022) - Normyle, Anna; Doran, Bruce; Vardon, Michael; Mathews, Dean; Melbourne, Julie
Abstract: Ecosystem accounting is emerging as a promising tool for environmental management by offering consistent information about ecosystem change over time. Via a United Nations process, ecosystem accounting has been standardised in the System of Environmental-Economic Accounting (SEEA). However, there are currently no examples of ecosystem accounts developed specifically to support Indigenous people's management of land or sea. More than 40% (3 million square kilometres) of Australia's land and sea territory has Indigenous Title. If Indigenous managers are to use ecosystem accounting, then it is essential for them to be involved in its development. We assessed how ecosystem accounts can be developed and applied in a manner that supports the management objectives of Indigenous owners and managers. Working collaboratively with the Yawuru Traditional Owners of the land and sea country around Broome, Western Australia, we constructed and assessed experimental ecosystem accounts for land cover and fire for the period 2000–2020. Three key benefits of ecosystem accounts for supporting the priorities of Yawuru managers were identified: (1) flexibility in the units used for the analysis; (2) the extended time scale of the accounts; and (3) the emphasis on consistent capturing and reporting of data. We also identified the need for further work to incorporate cultural knowledge and values within the broader SEEA, with implications for the recognition of Indigenous people, knowledge and values within accounting systems globally. Highlights: First example of ecosystem accounting development in an Indigenous context. Pilot land cover and fire accounts produced for a 20-year period 2000–2020. Assessment with Indigenous managers shows potential to support land management. Further work needed to integrate cultural values with SEEA-Ecosystem Accounting.